Epicardial blebs and septal hematoma after ventricular septal defect closure. (July 2020) - Jose, Joyce Mary; Padala, Sri Rama Ananta Nagabhushanam; Rajkumar, Sundararaj; Prasad, Sreevathsa KS; Jha, Ajay Kumar
Rapidly progressive epicardial hemorrhagic blebs during weaning from cardiopulmonary bypass after perimembranous ventricular septal defect closure has not been reported previously. Here, we describe the case of a 3-month-old baby with life-threatening epicardial hemorrhagic blebs and an interventricular septal hematoma after perimembranous ventricular septal defect patch closure.